Use of SF-501 as a Vascular Wall Protective Agent in Induced Atherogenesis in Experimental Animals. - Sawyer, F.N.; Stanczewski, B.; Schwann, G.; Freeman, L. (Thrombosis and Haemostasis, 1979)
SF-501 (p-carboxy phenyl ammonium ascorbate), a member of a family of vascular wall protective agents was given orally to a group of guinea pigs on atherogenic diet over a nine week period. At regular intervals serum cholesterol, triglyceride, RBC, WBC, Hematocrit, and hemoglobin levels were determined In addition to monitoring the weight loss/gain. This group was compared with a group of guinea pigs on atherogenic diet and a normal control group. At the end of the trial current induced thrombosis times of the mesenteric vessels were determined and all the organs of the body were preserved for histologic, and electron microscopic examination.The results clearly reveal that SF-501; (i) partially offsets the marked ‘runting’ of the animals on atherogenic diet (+ 4%-atherogenic diet; + 55%-atherogenic +- SF-501); (ii) the triglyceride levels are reduced (210 mg/dl-atherogenic diet; 46 mg/dl-atherogenic diet + SF-501);(iii) the gross he pa tody s trophy of the liver, visual changes in the vasculature of the kidney/Intestines and spleen, edema of the brain, hemorrhage and loss of Intima of major vessels brought about by the diet have been almost totally eliminated by co-in-jestion of SF-501. Statistical analysisof the data confirm the distinct protective effect of SF-501 on the blood vessel wall and other tissues of animals on atheroRenic diet.